The Nimrod transmembrane receptor Eater is required for hemocyte attachment to the sessile compartment in Drosophila melanogaster - Bretscher, Andrew J. (Biol Open, 2015)
Eater is an EGF-like repeat transmembrane receptor of the Nimrod family and is expressed in Drosophila hemocytes. Eater was initially identified for its role in phagocytosis of both Gram-positive and Gram-negative bacteria. We have deleted eater and show that it appears to be required for efficient phagocytosis of Gram-positive but not Gram-negative bacteria. However, the most striking phenotype of eater deficient larvae is the near absence of sessile hemocytes, both plasmatocyte and crystal cell types. The eater deletion is the first loss of function mutation identified that causes absence of the sessile hemocyte state. Our study shows that Eater is required cell-autonomously in plasmatocytes for sessility. However, the presence of crystal cells in the sessile compartment requires Eater in plasmatocytes. We also show that eater deficient hemocytes exhibit a cell adhesion defect. Collectively, our data uncovers a new requirement of Eater in enabling hemocyte attachment at the sessile compartment and points to a possible role of Nimrod family members in hemocyte adhesion.